If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-40)(x+30)=97317
We move all terms to the left:
(x-40)(x+30)-(97317)=0
We multiply parentheses ..
(+x^2+30x-40x-1200)-97317=0
We get rid of parentheses
x^2+30x-40x-1200-97317=0
We add all the numbers together, and all the variables
x^2-10x-98517=0
a = 1; b = -10; c = -98517;
Δ = b2-4ac
Δ = -102-4·1·(-98517)
Δ = 394168
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{394168}=\sqrt{4*98542}=\sqrt{4}*\sqrt{98542}=2\sqrt{98542}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-10)-2\sqrt{98542}}{2*1}=\frac{10-2\sqrt{98542}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-10)+2\sqrt{98542}}{2*1}=\frac{10+2\sqrt{98542}}{2} $
| 5y-(-1)=12 | | 2654=42(p+20) | | 4x-5(3x=10)=126 | | 8+6xx=5 | | 38b=4(4b-1) | | 5+-5x=12-4x | | 2976=31(p+15) | | 5h+11=41h= | | 3x-72+x+5+x+-3=180 | | 7x-5x=6x+7 | | 5.z-12=0 | | 5b+6=3b | | 2^(3x-4)=7^x | | 9y+2=10y | | 9(2-q)=3(q-12) | | 6a+a=7a | | 3x²+6x=85 | | 5/7=8/b | | ⅔b+5=20−b | | 9/b=10/9 | | 26.8=6.7Xn | | 8x+12=2x+18 | | x-3.89=1.1 | | 2(-9-3x)=-12 | | -2(3+x)=-10 | | 9(2x)+1=72 | | 1+x/2=x | | 5x^2+5x=2100 | | -9(-2-4x)=54 | | 1+.5x=x | | 5(-2-x)=-15 | | 9x+2x-3x-5=11 |